2012
DOI: 10.1007/978-3-642-33660-7
|View full text |Cite
|
Sign up to set email alerts
|

Instruments and Methods for the Radio Detection of High Energy Cosmic Rays

Abstract: Instruments and Methods for the Radio Detection of High Energy Cosmic RaysCosmic rays at energies above 10 15 eV cannot be measured directly due to the low flux. Instead, the properties of the primary cosmic ray particles (arrival direction, energy, mass) have to be reconstructed from measurements of secondary particles forming an air shower. For this, digital radio antenna arrays, like LOPES at the Karlsruhe Institute of Technology (KIT), are a relatively new instrument. The radio emission mainly originates f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 77 publications
0
16
0
1
Order By: Relevance
“…Until now, the sensitivity of radio measurements to the longitudinal air-shower development was predicted by simulations of the radio emission [8], but the experimental proof was still missing. We supply this proof by comparing the mean pseudorapidities of muons measured by KASCADE-Grande with the slope of the radio lateral distribution measured with LOPES [7,9,10], a digital radio-antenna array co-located with KASCADEGrande. LOPES features a precise time [11] and absolute amplitude calibration [12], and measures the radio signal between 40 and 80 MHz.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, the sensitivity of radio measurements to the longitudinal air-shower development was predicted by simulations of the radio emission [8], but the experimental proof was still missing. We supply this proof by comparing the mean pseudorapidities of muons measured by KASCADE-Grande with the slope of the radio lateral distribution measured with LOPES [7,9,10], a digital radio-antenna array co-located with KASCADEGrande. LOPES features a precise time [11] and absolute amplitude calibration [12], and measures the radio signal between 40 and 80 MHz.…”
mentioning
confidence: 99%
“…Furthermore, we apply several cuts on the LOPES measurement accepting only events with a radio signal clearly distinguishable from noise. Of those events passing these cuts we exclude 1 event recorded during a thunderstorm, and 19 events for which the fit of the exponential-lateral-distribution function fails (see reference [10] for a description of the cuts). To eliminate scattered, low-energy muons from the analysis [5], we use only muon tracks with ρ < 8 • and τ < 2 • .…”
mentioning
confidence: 99%
“…As a rule, in experiments with antennas operating at an effective frequency bandwidth [ω 0 , ω 0 + ∆ω] the radio signal E ω 4 is defined as the ratio of the maximum instantaneous amplitude of the En[e ω (t)] to ∆ω [38]:…”
Section: Jcap12(2012)029mentioning
confidence: 99%
“…Furthermore, LOPES has shown that the radio amplitude is roughly proportional to the primary energy -as expected for any coherent radio emission process -and that the arrival direction can be reconstructed with an accuracy of 1.5 • (Nigl et al, 2008). For the reconstruction of the primary mass there are two promising ways under study: First the shape of the radio wavefront (Lafebre et al, 2010;Schröder et al, 2010c), and second the slope of the lateral distribution of the radio emission (Huege et al, 2008). The evaluation of the first way is still in progress, but results from the latter one are presented in the next paragraph.…”
Section: Setup and Preparatory Workmentioning
confidence: 99%